Internal Structure Test of Big Five Inventory - Sutejo, Agus; Siaputra, Ide Bagus; Lasmono, Hari K. (ANIMA Indonesian Psychological Journal, 2011)
The purpose of this study was to explain the internal structure of Big Five personality trait instrument, namely the Big Five Inventory (BFI). Maximum likelihood method of factor analysis in SPSS 16.0 was used to find suitability between the model proposed and data collected. Subjects (N=156) were all psychology students. Results reveal that five factors personality (Big Five) as proposed by personality theory is not in accordance with data collect- ed. Seven factor model is more appropriate to explain personality, namely openness to ex- perience, conscientiousness, friendliness, introversion, emotional stability, aggressiveness, and vulnerability. The findings have two alternative meanings, first an essential difference in meaning derived from the translated instrument items that could exhibit different responses, and second, the large spectrum of personality characteristics in "Big Five" enables the emergence of a new form of different personality characteristic as a consequence of overlapping between factors of the theory. Penelitian ini berusaha menjelaskan struktur internal alat ukur big five personality trait, yakni Big Five Inventory (BFI). Metode yang digunakan adalah analisis faktor menggunakan metode maximum likelihood dalam program SPSS 16.0 untuk mencari kesesuaian model yang diajukan dengan data yang diperoleh. Subjek (N=156) adalah mahasiswa psikologi. Hasilnya menunjukkan bahwa model lima faktor yang diajukan dalam teori kepribadian big five tidak sesuai dengan data yang didapatkan. Adapun, model tujuh faktor lebih cocok untuk menjelaskan kepribadian dalam subjek penelitian ini. Tujuh faktor itu terdiri atas openness, conscientious- ness, friendliness, introversion, emotional stability, aggressiveness, dan vulnerability. Perlu diperhatikan bahwa terdapat dua alternatif pemaknaan dalam temuan ini. Pertama adanya perbedaan esensi makna pada terjemahan butir alat ukur yang mungkin memunculkan perbedaan respons. Kedua adalah luasnya karakteristik kepribadian Big Five yang memungkin- kan terbentuknya karakteristik kepribadian yang berbeda akibat singgungan antar-faktor dalam teori tersebut.